2019
DOI: 10.1111/joim.12847
|View full text |Cite
|
Sign up to set email alerts
|

Mon2 predicts poor outcome in ST‐elevation myocardial infarction

Abstract: Aims There are limited data on the role of human monocyte subsets in ST‐elevation myocardial infarction (STEMI). The study aimed to establish the relationship between monocyte subsets, their phagocytic and nuclear factor κB (NFκB) activity and outcomes in STEMI. Methods Monocyte subsets and their phagocytic activity and intracellular levels of inhibitory κB kinase β (IKKβ, marker of NFκB activity) were measured by flow cytometry in 245 patients with STEMI, median follow‐up of 46 months. Results Mon2 (CD14++CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…23 Monocyte subsets were implicated in the pathophysiology of acute myocardial infarction and correlated with outcome and left ventricular function in those patients. [33][34][35] The detailed mechanisms are not understood; therefore, one could speculate that the observed monocyte subset changes in our study might be due to myocardial injury.…”
Section: Discussionmentioning
confidence: 85%
“…23 Monocyte subsets were implicated in the pathophysiology of acute myocardial infarction and correlated with outcome and left ventricular function in those patients. [33][34][35] The detailed mechanisms are not understood; therefore, one could speculate that the observed monocyte subset changes in our study might be due to myocardial injury.…”
Section: Discussionmentioning
confidence: 85%
“…LPS stimulation led to a significant increased production of TNF-α under all conditions and further, cryopreserved MNCs produced significantly higher amounts compared to fresh ones (Fresh 1049 pg/mL [543.2-3627], CS 6674 pg/mL [1694-10,200], SF 3977 pg/mL [690.5-5680], FBS 5754 pg/mL [644.4-12,060], RPMI 8690 pg/mL [994. [3][4][5][6][7][8][9][10]311]) (Figure 5F). Thus, although MNCs preserved their ability to react to inflammatory stimuli after freeze-thawing, cryopreservation of MNCs can affect the inflammatory readouts observed.…”
Section: Changes In the Immunological Response To Bacterial Lipopolys...mentioning
confidence: 99%
“…The analysis of human mononuclear cells (MNCs), which comprise circulating monocytes and lymphocytes, has become an invaluable tool in medical research and nowadays even in experimental clinical cell-therapies including autologous dendritic cell and chimeric antigen receptor T (CAR-T) cell immunotherapy [1][2][3][4]. Further, the absolute amounts and the relative composition of individual leukocyte populations can be used as reliable biomarkers and predictors in different (inflammatory) diseases, i.e., an increase of circulating CD14 ++ CD16 + CCR2 + intermediate monocytes (Mon2) was found to be independently predictive for cardiovascular events or outcome in multiple cardiovascular diseases [5][6][7][8]. Functional immunological assessment of MNCs ex vivo has further important implications in basic [9] as well as in therapeutic immunological research, as has been shown, for 2 of 20 example, in the assessment of vaccine-induced cell-based immune responses during the COVID-19 pandemic [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Mon1 represent the highest proportion of the monocytes (≈85%), while Mon2 and Mon3 represent about 5 and 10%, respectively 14 . Our group has demonstrated that high absolute Mon1 counts during acute MI were associated with more major adverse cardiovascular events (MACE) 15 and worse myocardial salvage and convalescent left ventricular ejection fraction (LVEF) 16 . Higher baseline counts of Mon1 and Mon2 were positively associated with baseline and 6-month follow-up global longitudinal strain (GLS) 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Higher post-MI Mon2 counts were independently predictive of MACE and heart failure (HF). Also, higher intracellular levels of inhibitory κB kinase β (IKKβ), which is a cytoplasmic marker of activation of the nuclear factor-κB (NFκB) pathway, were associated with tenfold lower occurrence of HF 15 .…”
Section: Introductionmentioning
confidence: 99%